A Robust Bioassay of the Human Bradykinin B2 Receptor That Extends Molecular and Cellular Studies: The Isolated Umbilical Vein - François Marceau; Hélène Bachelard (MDPI AG, 2021)
Bradykinin (BK) has various physiological and pathological roles. Medicinal chemistry efforts targeted toward the widely expressed BK B2 receptor (B2R), a G-protein-coupled receptor, were primarily aimed at developing antagonists. The only B2R antagonist in clinical use is the peptide icatibant, approved to abort attacks of hereditary angioedema. However, the anti-inflammatory applications of B2R antagonists are potentially wider. Furthermore, the B2R antagonists notoriously exhibit species-specific pharmacological profiles. Classical smooth muscle contractility assays are exploited over a time scale of several hours and support determining potency, competitiveness, residual agonist activity, specificity, and reversibility of pharmacological agents. The contractility assay based on the isolated human umbilical vein, expressing B2R at physiological density, was introduced when investigating the first non-peptide B2R antagonist (WIN 64338). Small ligand molecules characterized using the assay include the exquisitely potent competitive antagonist, Pharvaris Compound 3 or the partial agonist Fujisawa Compound 47a. The umbilical vein assay is also useful to verify pharmacologic properties of special peptide B2R ligands, such as the carboxypeptidase-activated latent agonists and fluorescent probes. Furthermore, the proposed agonist effect of tissue kallikrein on the B2R has been disproved using the vein. This assay stands in between cellular and molecular pharmacology and in vivo studies.